PENYULUHAN PENERAPAN TEKNOLOGI IOT (INTERNET OF THINGS) DI BERBAGAI BIDANG SMAN 18 KABUPATEN TANGERANG - Yogi Priyo Istiyono; Sartono Sartono; Siti Fatimatul Zuhro; Nirfison Nirfison; Rahman Soesilo (Jurnal Abdimas Bina Bangsa, 2023)
Community service in the form of IoT (Internet of Things) technology outreach in various fields aims to provide understanding and skills to students of SMAN 18 tangerang regency. regarding the application of this technology. Through this outreach, it is expected that students will comprehend the potential and application of IoT technology in their daily lives. The outreach utilizes educational methods such as presentations, interactive discussions, and practical demonstrations. Basic knowledge of IoT, connectivity concepts, and its benefits in fields such as healthcare, agriculture, energy, and the environment is taught to the students. Additionally, hands-on practice in building and connecting IoT devices is conducted to provide a deeper understanding. The results of this outreach show an improvement in participants' understanding and interest in IoT technology. Students also acquire fundamental skills in designing, implementing, and managing simple IoT projects. The implementation of IoT technology in various fields, such as remote patient monitoring in healthcare, can bring significant benefits to the community surrounding SMAN 18 tangerang regency